A Randomized Controlled Trial Comparing Polyethylene Glycol with Sodium Phosphate for Gut Preparation in children undergoing Proctoscopy - Umair Khaliq Siddiqi, Muhammad Sharif, Hafiza Mariam Rafiq, Hamza Malik, Muhammad Kashif Bashir, Hafiz Muhammad Adnan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The outcome of diagnostic and therapeutic procedures such as proctoscopy, colonoscopy, and endoscopy relies on thorough bowel preparation, ensuring a complete view of the colonic mucosa. Aim: To compare polyethylene glycol with sodium phosphate for gut preparation in children undergoing proctoscopy. Methods: We conducted a study on pediatric patients aged 3 to 14 years who underwent elective proctoscopy. The study took place in the pediatric surgical ward of Mayo Hospital, Lahore, following approval from the hospital's Ethical Committee. We educated the parents or guardians of patients preoperatively about the use of bowl preparatory agents, their effectiveness, outcomes, side effects, complications, and informed consent. We divided the children into two groups to determine the method of bowl preparation. Patients in Group 'A' underwent bowl preparation using polyethylene glycol. Results: There were 60 patients, with 30 in each group. Patients in Group 'A' were given bowl preparation with polyethylene glycol. Before the proctoscopy, the patients underwent a 1-day PEG 3350 bowel preparation regimen. While group B had bowel preparation with sodium phosphate enema, the patients' mean ages were 4.46 years. In group A, there were 16 males and 14 females, while in group B, there were 19 males and 11 females. In group A, 11 patients demonstrated excellent compliance, 12 showed partial compliance, and 7 showed poor compliance with polyethylene glycol. While in group B, 22 patients showed excellent compliance, and 8 patients showed good compliance. Practical Implication: The study suggests that both polyethylene glycol (PEG) and sodium phosphate enema are suitable for pediatric patients undergoing proctoscopy. However, compliance rates vary between the two methods. Patients in group A showed varying levels of compliance, while those in group B showed higher compliance. Therefore, healthcare providers should consider sodium phosphate enema for improved patient adherence and procedural outcomes. This highlights the importance of assessing compliance rates for informed decision-making. Conclusion: In our experience, sodium phosphate enema was superior to oral polyethylene glycol in terms of compliance and adequacy of gut preparation. There were also fewer side effects with the sodium phosphate enema. Keywords: Polyethylene glycol, proctoscopy, gut preparation